Direct measurement of the magnetic anisotropy field in Mn-Ga and Mn-Co-Ga Heusler films - Fowley, Ciaran; Ouardi, Siham; Kubota, Takahide; Yildirim, Oguz; Neudert, Andreas; Lenz, Kilian; Sluka, Volker; Lindner, Juergen; Law, Joseph M.; Mizukami, Shigemi; Fecher, Gerhard H.; Felser, Claudia; et al. (Journal of Physics D: Applied Physics, 2015)
The static and dynamic magnetic properties of tetragonally distorted Mn-Ga based alloys were investigated. Static properties are determined in magnetic fields up to 6.5 T using SQUID magnetometry. For the pure Mn1.6Ga film, the saturation magnetisation is 0.36 MA m-1 and the coercivity is 0.29 T. Partial substitution of Mn by Co results in Mn2.6Co0.3Ga1.1. The saturation magnetisation of those films drops to 0.2 MA m-1 and the coercivity is increased to 1 T. The time-resolved magneto-optical Kerr effect (TR-MOKE) is used to probe the high-frequency dynamics of Mn-Ga. The ferromagnetic resonance frequency extrapolated to zero-field is found to be 125 GHz with a Gilbert damping, α, of 0.019. The anisotropy field is determined from both SQUID and TR-MOKE to be 4.5 T, corresponding to an effective anisotropy density of 0.81 MJ m-3. Given the large anisotropy field of the Mn2.6Co0.3Ga1.1 film, pulsed magnetic fields up to 60 T are used to determine the field strength required to saturate the film in the plane. For this, the extraordinary Hall effect was employed as a probe of the local magnetisation. By integrating the reconstructed in-plane magnetisation curve, the effective anisotropy energy density for Mn2.6Co0.3Ga1.1 is determined to be 1.23 MJ m-3.
CRIS-Team Scopus Importer:2023-03-20
Keywords: coercivity; Hall effect; Heusler films; magnetic anisotropy; time-resolved magneto-optical Kerr effect